PENGELOLAAN AKUN TIKTOK @DEUTSCHKURSEBILDUNG DALAM EDUKASI BAHASA JERMAN - Azzahra, Adinda; Ramdani, Guruh; Fachrurrizal, Fikry (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This study examines the management strategy of the TikTok account @deutschkursebildung as a German language education medium, with a focus on the implementation of Social Media Management Theory and POAC Theory (Planning, Organizing, Implementing, Monitoring). Using qualitative methods through observation, active participation, interviews, and literature review, the study involved account managers as key informants. The results show that content management is carried out systematically with an educational entertainment approach, incorporating elements of entertainment and education through memes, digital trends, and dynamic visualizations that attract young audiences. The planning process includes content meetings and calendar content for consistency, organization through task allocation, creative implementation with trend adaptation, and TikTok data-based monitoring for performance evaluation. The main challenges are the balance between educational entertainment, idea fluctuations, and platform algorithms, which are addressed through adaptive strategies such as brainstorming and format experimentation. The conclusion confirms that the account's success depends on creativity, team coordination, and data evaluation, providing insights for the development of responsive and innovative digital educational media. ABSTRAK Penelitian ini menelaah strategi pengelolaan akun TikTok @deutschkursebildung sebagai media edukasi Bahasa Jerman, dengan fokus pada implementasi Teori Manajemen Media Sosial dan Teori POAC (Perencanaan, Pengorganisasian, Pelaksanaan, Pengawasan). Penelitian ini menggunakan metode kualitatif melalui observasi, partisipasi aktif, wawancara, dan studi pustaka dengan melibatkan pengelola akun sebagai informan utama. Hasil menunjukkan bahwa pengelolaan konten dilakukan secara sistematis dengan pendekatan hiburan edukatif, memasukan unsur hiburan dan edukasi melalui meme, tren digital, dan visualisasi dinamis yang menarik audiens muda. Proses perencanaan meliputi pertemuan konten, dan konten kalendar untuk konsistensi, pengorganisasian melalui pembagian tugas, pelaksanaan kreatif dengan adaptasi tren, serta pengawasan berbasis data TikTok untuk evaluasi performa. Tantangan utama adalah keseimbangan edukasi hiburan, fluktuasi ide, dan algoritma platform, diatasi dengan strategi adaptif seperti bertukar pikiran dan eksperimen format. Kesimpulan menegaskan bahwa keberhasilan akun bergantung pada kreativitas, koordinasi tim, evaluasi data, memberikan wawasan untuk pengembangan media edukasi digital yang responsif dan inovatif.